DIALEKTIKA BAHASA JAWA DALAM ADAT PERANG BANGKAT SUKU OSING KECAMATAN SINGOJURUH - Ahmad Sulthoni; Dhalia Soetopo (Khazanah Pendidikan, 2020)
ABSTRACTPerang Bangkat Ceremony is one proof of the diversity of cultures in Banyuwangi. Thiscustom is held at a bride and groom event at the Osing tribe, but not all weddinggatherings use the Perang Bangkat Ceremony. Perang Bangkat is used when the brideis the eldest and youngest child in her family.The Osing people believe that if the eldestchild marries the youngest child, then in his household there will be many problems ortemptations that occur. This is where the osing community feels it is necessary to do thePerang Bangkat in the event of a wedding gathering which is intended to keep theobstacles or obstacles in the household that will be lived by the bride and groom. Withthe above conditions it can be known at this time that very few people understand theJavanese language spoken at the traditional ceremony of the Perang Bangkat. So thatin determining the respondents the author uses the snowball method. The data collectionused the method of observation, interviews and documentation. From the explanationabove, the writer would like to examine further the meaning contained in the BangkatCustomary Ceremony as an effort to increase knowledge about Javanese language andcultural heritage which are intended to increase love and care for the BangkatCustomary Customs in the modernization era. Therefore the authors feel the need tofurther study the customs of warfare and conduct research with the title "Dialogue ofJavanese Language in the Form of Osing Tribal War Sing Singuruh Subdistrict" Themethod used in descriptive qualitative data analysis with interactive analysis techniquesand using the checking of findings by triangulation source.Keywords: Javanese dialectic, Perang Bangkat